Controlling Aqueous Self‐Assembly Mechanisms by Hydrophobic Interactions. Issue 43 (8th September 2014) - Rudolph, Tobias; Kumar Allampally, Naveen; Fernández, Gustavo; Schacher, Felix H.
Abstract We report an innovative template‐assisted synthetic protocol for the selective functionalization of terminal triple bonds in oligophenyleneethynylenes (OPE) by pre‐organization in aqueous solution. By this approach, three new OPE‐based bolaamphiphiles substituted with hydrophilic poly(2‐ethyl‐2‐oxazoline) (PEtOx) chains of different length have been synthesized. The chain length was observed to strongly influence the aqueous supramolecular polymerization: bolaamphiphiles with longer hydrophilic chains aggregate into spherical nanoparticles in a stepwise fashion, whereas 2D anisotropic platelets are formed cooperatively if shorter PEtOx chains are used. Our results demonstrate that hydrophobic interactions can be strong enough to trigger cooperative effects in aqueous self‐assembly processes.